A method for accurate positioning of auricular acupoints (一种便于定位耳穴的方法研究) - XIANG Yiming (向毅明); XIE Wei (谢薇); REN Xiuya (任秀亚); YUAN Dan (袁丹); ZHAO Lingling (赵玲玲); ZHOU Yihan (周艺涵); LUO Liyuan (罗丽媛) (Journal of International Translational Medicine Limited, 2023)
In order to make the positioning of auricular acupoints more accurate, the three-dimensional human ear model library has been established by using modern scientific and technological three-dimensional scanning and other equipments, and the auricular acupuncture operator obtained the patient's ear mold acupuncture point identification map through three-dimensional scanning, which simplifies the original complex ear acupuncture positioning and facilitates the positioning and extraction of acupuncture points, which is worthy of clinical promotion and application. (为使耳穴操作者定位更加精准, 利用现代科学技术三维扫描等设备建立三维人耳模型库, 耳穴操作者通过三维扫描获得患者的耳模穴位标识图, 使原本复杂的耳穴定位简单化, 便于定位取穴, 值得临床推广应用。)